The Everyday Environment: A Place to Feel Connected to, a Place that has Meaning - Blankman, Marian (Journal of Geography Education, 2022)
This paper reports on the findings of a research project investigating the connection of primary school students with their everyday environment and the meaning they derive from it. Children’s place attachment and sense of place are investigated using a mosaic approach. Through participatory research activities, such as map making, neighbourhood walks, and interviews, children described their connections, knowledge, meanings, and opinions about the environment. Results show that this approach provides structured insight into how well children are connected with their everyday environment and have developed insideness in their sense of place. How this insight can be used in primary Geography education is discussed.